The influence of virtual reality on rehabilitation of upper limbs and gait after stroke: a systematic review - Camargo, Alline; Carmo, Jaqueline Fernanda; Rosa-Castro, Raquel Mendonça; Rodrigues, Cristiane; Mazzei, Lauren Giustti; Scalha, Thais Botossi; Andrade, Ana Carolina Nunes Bovi (Journal of Innovation and Healthcare Management, 2019)
Stroke is the leading cause of functional disability in adults. Its neurovascular origin and injury location indicates the possible functional consequences. Virtual rehabilitation (VR) using patient’s motion control is a new technological tool for conventional rehabilitation, allowing patterns of movements in varied environments, involving the patient in therapy through the playful components offered by VR applications. The objective of this systematic review is to collect data regarding the influence promoted by VR in upper limb and hemiparetic gait. Full articles published between 2009 and 2015 in english were searched and selected in PubMed, Cochrane and Pedro databases. Eleven articles included (5 for VR and upper limbs; 4 for VR, gait and balance; and 2 for VR and neural mechanisms). The articles included demonstrate efficacy in VR treatment in hemiparetic patients in the variables analyzed.